Executive function differences as a function of parent‐reported binge eating and weight: Results from the adolescent brain cognitive development study - Kaitlin N. Rozzell‐Voss; Patrycja Klimek‐Johnson; Dawn M. Eichen; Tiffany A. Brown; Aaron J. Blashill (Wiley, 2024)
Abstract Background Binge eating is a relatively common disordered eating behavior among children, and is associated with poor health outcomes. Executive function (EF)-higher order cognitive abilities related to planning and impulse control-may be implicated in both binge eating and pediatric obesity. Although EF deficits are evident among individuals with obesity and/or binge eating, findings are mixed across the lifespan. Methods The present study examined differences in EF among children with varying weight statuses and parent‐reported binge eating. The sample included 10,017 children from the Adolescent Brain Cognitive Development study, aged 9-10 years. Results Children with parent‐reported binge eating-either with overweight/obesity or normal weight-had significantly lower EF than those with no binge eating and a normal weight status but did not differ from those with no binge eating and overweight/obesity. Children with no binge eating and overweight/obesity also had statistically significantly lower EF than those with normal weight status. Although all significant differences between groups were negligible to very small, results may indicate similar neurocognitive profiles among children with binge eating and those with overweight/obesity. Conclusions Alterations in EF among children with binge eating may not be solely related to weight‐specific factors, as significant differences also emerged among children with normal weight status, with versus without parent‐reported binge eating. Future research is needed to understand temporal associations between obesity, disordered eating, and neurocognition in children using multi‐informant methods for assessing binge eating.